Trichobilharzia regenti (Schistosomatidae): 3D imaging techniques in characterization of larval migration through the CNS of vertebrates. (April 2016) - Bulantová, Jana; Macháček, Tomáš; Panská, Lucie; Krejčí, František; Karch, Jakub; Jährling, Nina; Saghafi, Saiedeh; Dodt, Hans-Ulrich; Horák, Petr
Highlights: Larvae of bird schistosomes can be tracked by use of intravital fluorescent dyes. 3D imaging of schistosomes in tissues can be done by ultramicroscopy or micro-CT. These methods contribute to our knowledge of schistosome pathogenicity. Abstract: Migration of parasitic worms through the host tissues, which may occasionally result in fatal damage to the internal organs, represents one of the major risks associated with helminthoses. In order to track the parasites, traditionally used 2D imaging techniques such as histology or squash preparation do not always provide sufficient data to describe worm location/behavior in the host. On the other hand, 3D imaging methods are widely used in cell biology, medical radiology, osteology or cancer research, but their use in parasitological research is currently occasional. Thus, we aimed at the evaluation of suitability of selected 3D methods to monitor migration of the neuropathogenic avian schistosome Trichobilharzia regenti in extracted spinal cord of experimental vertebrate hosts. All investigated methods, two of them based on tracking of fluorescently stained larvae with or without previous chemical clearing of tissue and one based on X-ray micro-CT, exhibit certain limits for in vivo observation. Nevertheless, our study shows that the tested methods as ultramicroscopy (used for the first time in parasitology) and micro-CT represent promising tool for precise analyzing of parasite larvae in the CNS. Synthesis of these 3D imaging techniques can provide more comprehensive look at the course of infection, host immune response and pathology caused by migrating parasites within entire tissue samples, which would not be possible with traditional approaches.